The failure of former African liberation movements to transition to democracy after ascension to power: a descriptive analysis of eritrean people's liberation front - Idris, Idris Mahmoud; Elfatih, Abdelsalam Abdullahi; Zaroum, AbdulHamid Mohamed Ali (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 2021)
This paper investigates the perplexing issue of the democratic deficit in Africa's postliberation states. It seeks to answer why former African liberation movements failed to make a genuine transition to democracy during the second stage of the national liberation struggle, instead ofleaving behind authoritarian military regimes and one-party states that disappointed people. The paper's primary goal is to study the transitional path offormer liberation movements in Africa and examine thefactors that contribute to thefailure ofthe transformation process from armed resistance to conventional politics. The research is descriptive and analytical in nature, conducted using the qualitative research method The findings show that former liberation movements in Africa failed as governments due to a variety offactors, the most important ofwhich is elite resistance to democratisation, which led to the transition to dictatorship, the absence or weakness of political institutions due to the persistence of the liberation era's political culture, and the tinkering with the constitution and failure to put some of its key principles into effect. Furthermore, the study showed that anti-colonial revolutions in Africa only liberated the state, not the people. Finally, the paper ends with some recommendations i.e. several steps to be taken in order for African countries to overcome the dilemma of the liberation movement's democratic transition failure. Keywords: Eritrea, EPLF, Liberation Movements, Urica, Transition to Democracy, Failure